Do post-COVID-19 symptoms exist? A longitudinal study of COVID-19 sequelae in Wenzhou, China - Zhou, Min; Cai, Jing; Sun, Wenjie; Wu, Jing; Wang, Yidong; Gamber, Michelle; Fan, Lingyan; He, Guiqing (Annales médico psychologiques, 2021)
We conducted a cohort of tracing discharge patients of COVID-19. We used the Mann–Whitney U test, χ2 test, or Fisher's exact test to compare differences between age groups and gender groups where appropriate. Our study provides insights into the nature and severity of medical conditions specific to survivors of COVID-19. It also highlights the potential mental health issues resulting from infectious disease outbreaks within communities. Nous avons suivi une cohorte de patients à la sortie du COVID-19. Nous avons utilisé les test de Mann–Whitney U, de Fisher ou du Chi2 pour comparer les différences entre les groupes d’âge et de genre, le cas échéant. Notre étude fournit un aperçu de la nature et de la gravité des troubles médicaux propres aux survivants du COVID-19. Elle met également en lumière les problèmes de santé mentale potentiels découlant des éclosions de maladies infectieuses dans les collectivités.